Increased count of Bacteroides fragilis in the feces of palmar arsenical keratosis patient (Bangladesh Journal of Pharmacology, 2016)
Chronic exposure to high concentration of arsenic caused an increase in the colony count of Bacteroides fragilis in the feces in comparison to healthy volunteer (3.6 × 10¹¹ ± 1.9 vs 1.5 × 10¹¹ ± 1.7 CFU/g of feces) which was not statistically significant. But significant increase in the colony count of B. fragilis was seen in the feces of palmar arsenical keratosis patient (4.2 × 10¹¹ ± 1.9 CFU/g of feces; p=0.0390). Supplementation with probiotic for 12 weeks decreased the colony counts in all three groups which were not statistically significant among the groups. Probiotics decreased the amount of arsenic in the nail of all the three groups significantly.